Ornithical community of Vallombrosa Biogenetic National Nature Reserve (Italy). Issue 1 (1st January 2021) - Martini, I.; Galipò, G.; Foderi, C.; Tocci, R.; Sargentini, C.
Abstract: The aim of this work was to monitor the ornithic community of the forest of Vallombrosa Biogenetic National Nature Reserve, in the Florence area. The forest covers about 1273 hectares, at an altitude of 470 to 1440 m above sea level (a.s.l.). The main forest types are coniferous woodland, mixed woodland of coniferous and deciduous trees with a prevalence of beech, and open areas. The bird monitoring was carried out using the point count method. Forty-one listening points were considered. The results of the counts allowed the calculation of abundance per station (n), richness (S), Shannon–Wiener diversity (H'), evenness (J') and non-passerine incidence (NP). The data were analysed using the Kruskal–Wallis non-parametric test and principal component analysis, considering the forest type, season and altitude as sources of variability. Forty-seven bird species were identified. Abundance was higher in open areas, in the pre-reproductive period and at 800–1000 m a.s.l. Richness was higher in open areas, in reproductive and pre-reproductive periods and at lower altitudes. Diversity index was higher in open areas, in the reproductive period and at lower altitudes. Evenness was greater in the reproductive period, lower in the broadleaved-tree woodland and lower at higher altitudes. Non-passerine incidence was lower in deciduous areas, higher in the pre-reproductive and reproductive periods and higher at lower altitudes. Seventeen species registered more than 100 contacts each. The highest average values of richness, abundance, diversity and non-passerine incidence were found in the open areas and at high altitudes. Considering the ornithical community throughout the year, the ecological indices taken together showed the highest values in the pre-reproductive and reproductive periods. Because of the area's high richness and biodiversity, and the significant presence of species that are rare and of naturalistic interest, Vallombrosa forest is confirmed to be of high ornithological value.